HUBUNGAN ANTARA STRATEGI KOPING KELUARGA DAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PENYINTAS COVID-19 - SALSA ADELIA RAHMADANI; Erwin Erwin; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Introduction: Strong family support and the selection of appropriate family coping strategies are thought to reduce anxiety in Covid-19 survivors or the community. The purpose of this study was to determine the relationship between family coping strategies and family support with the anxiety level of Covid-19 survivors. Methods: This study used a retrospective study. The number of samples used in this study were 86 people who were taken using purposive sampling technique. Data collection was taken using the Zung Sel-Rating Anxiety Scale questionnaire, family support questionnaire and family coping strategies where the family support questionnaire and family coping strategies have been modified and have been tested for validity and reliability. The data analysis used is univariate and bivariate using Chi-square test. Results: The description of the strategy in the medium category was 61 respondents (70.9%), high family support was 46 respondents (53.5%), and the category of mild anxiety was 57 respondents (66.3%). Bivariate analysis showed that there was no significant relationship between family coping strategies and the anxiety level of Covid-19 survivors (p-value = 0.701) and there was no significant relationship between family support and anxiety levels of Covid-19 survivors (p-value = 0.694) Conclusion: The results of this study found that the current level of anxiety experienced by Covid-19 survivors did not affect family support or family coping strategies.Keywords: Anxiety, Coping Strategies, Family, Covid-19 Survivor